النقد العربي المقارن: عبد القاهر الجرجاني في ميزان النقد المقارن نَمُوذَجاً /Arabic Comparative Criticism: A Critical Study on Abd al-Qahir Al-Jurjani - Hanadi Muhammad Behairi, (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2023)
ملخص البَحث: النقد المقارن حقل معرفي خصب، يمكن من خلاله الموازنة بين النقد العربي وغيره من اللغات الأخرى، لتقريب النقد العربي مع النقد الناشئ في بيئات وثقافات إنسانية مشتركة؛ حيث أفرزت توجهات، وأنجبت شخصيات نقدية جديرة بالدراسة والتمحيص في مجالها الفكري، ويبقى النقد العربي في معزل عن هذه الدراسات على المستوى الثقافي والأكاديمي. ويبرز البحث الفرق بين مصطلحي النقد المقارن والأدب المقارن باستخدام المنهج الوصفي الاستقرائي، وتسليط الضوء على الناقد عبد القاهر الجرجاني (ت 471ه) رائد نظرية النظم في البلاغة العربية، وجهود الباحثين في إبراز قيمته الفكرية عبر المقارنة بغيره من النقاد في اللغات الأخرى. توصلت الدراسة إلى عدم وجود منهجية بحثية محددة في مجال النقد المقارن يفتح باب المعرفة على مصراعيه؛ ليبذل الباحث ويقدم خلاصة فكره لتطوير الفكر النقدي، وتجلياته في اللغات الأخرى. لقد أسهم الغرب في نشأة هذا المصطلح، وتغذيته وكان عبد القاهر الجرجاني من أهم الشخصيات النقدية العربية الذي ينبغي أن يحظى بدراسات مقارنة نقدية، بينه وبين النقاد الآخرين في اللغات الأخرى للوصول إلى عالمية النقد العربي ولمواكبة النقد العالمي. الكلمات المفتاحية: النقد المقارن، عبد القاهر الجرجاني، النقد الثقافي، نقد النقد، الأدب المقارن. Abstract: Comparative criticism is a fertile field of knowledge, through which it is possible to balance between Arabic criticism and other languages, thus bringing Arab criticism closer to the arising criticism in common human cultures and environments; where it produced directions and developed critics that are worthy of study in their intellectual field. However, Arab criticism remains isolated from these studies on the cultural and academic level. The research highlights the difference between the terms comparative criticism and comparative literature using the descriptive inductive approach and shedding light on the critic Abd al-Qahir al-Jurjani (d. 471 AH), the pioneer of Al-Nazm theory in Arabic rhetoric, and the efforts of researchers to highlight his intellectual value compared to other critics in other languages. The study concluded that there is no specific research methodology in the field of comparative criticism that opens the door of knowledge wide for the researcher to exert and present a summary of his idea to develop critical thinking and its manifestations in other languages. Indeed, the West contributed to the emergence of this term and its nourishment. Abd al-Qahir al-Jurjani was one of the most important figures of Arab critics who should receive critical comparative studies between him and other critics in other languages in order to reach the universality of Arab criticism and to keep pace with international criticism. Keywords: comparative criticism, Abd al-Qahir al-Jurjani, cultural criticism, criticism of criticism, comparative literature Abstrak Kritikan perbandingan adalah bidang ilmu yang sentiasa berkembang, yang melaluinya kita boleh mengimbangi antara kritikan sastera Arab dan bahasa-bahasa lain. Selain itu, ia juga untuk mendekatkan kritikan Arab kepada kritikan yang lahir dalam pelbagai budaya dan persekitaran manusia yang mempunyai persamaan. Bidang ini telah berjaya menghasilkan pelbagai pemikiran dan melahirkan tokoh-tokoh pengkritik yang pemikiran mereka layak untuk dikaji dan diteliti. Sungguhpun begitu, kritikan Arab tetap terasing daripada kajian-kajian ini di peringkat budaya dan akademik. Kajian ini menyerlahkan perbezaan antara istilah kritikan perbandingan dan kesusasteraan perbandingan menggunakan pendekatan deskriptif-induktif, selain mengkaji idea Abdul Qahir Al-Jurjani (meninggal 471H), yang merupakan pelopor teori Al-Nazm dalam retorik Arab. Kajian juga membahaskan tentang usaha-usaha pengkaji dalam menonjolkan nilai pemikirannya dengan membandingkannya dengan pengkritik-pengkritik sastera bahasa lain. Kajian merumuskan bahawa tiada metodologi kajian khusus dalam bidang kritikan perbandingan yang memudahkan pengkaji untuk membentangkan rumusan ideanya sekaligus mengembangkan pemikiran kritis dan manifestasinya dalam bahasa lain. Sarjana barat mempunyai sumbangan kepada kemunculan istilah ini. Abdul Qahir Al-Jurjani adalah salah seorang tokoh kritikan sastera Arab yang selayaknya dikaji secara perbandingan kritis antara beliau dan pengkritik lain dalam bahasa lain untuk mencapai kesejagatan kritikan Arab, agar ia sejajar dengan kritikan global. Kata kunci: Kritikan perbandingan, Abdul Qahir Al-Jurjani, kritikan budaya, kritikan kritikan, sastera perbandingan